Categorization of R134a flow-induced vibration and noise in multi-conditions and effect of thermal load on the vibration in automobile air conditioning - Xin-Gang Zhu; Dong-Qing Zhu; Ming-Yu Shi; Zhi-Fu Zhou; Qin Zhao; Wen-Yu Jia; Ji-Xin Zhang; Rui Zhang (Case Studies in Thermal Engineering)
The gurgling and hiss noise near thermal expansion valve (TXV) in automobile air conditioning gradually become prominent. However, the causes of noise from the flow-induced vibration (FIV) have not been confirmed. In this paper, the vibration, noise and R134a-flow patterns are recorded synchronously to investigate the FIV causes in multi-conditions. Based on different flow patterns at TXV inlet, all conditions are categorized into four types to explore the relationship of flow patterns, FIV and noise. Then two causes are summarized. Firstly, the intermittent liquid-phase FIV is attributed to the intensive evaporation in a throttling process and mainly occurs in transition from liquid-phase flow to mist flow. Secondly, the sustaining two-phase FIV occurs as long as the gas of two-phase flow accelerates through TXV. For liquid-phase FIV, the pressure drop in two-phase region and vapor quality determined by thermal load always show positive correlation with vibration. For two-phase FIV, the annular-wavy flow increases amplitude of vibration peaks, but they are distributed at the similar frequency band regardless of thermal load and flow pattern. The vibration peaks of X, Y and Z are mainly distributed at 6000 Hz–9000 Hz. Decreasing thermal load reduces Y-vibration peak by 83.7 %.